ANG II- and TxA2-induced mesenteric vasoconstriction in rats is mediated by separate cell signaling pathways - Bauer, Johannes; Dau, Cécile Ngoc Dung; Cavarape, Alessandro; Schaefer, Franz; Ehmke, Heimo; Parekh, Niranjan (American journal of physiology. Heart and circulatory physiology, 1999)
Studies in vitro have demonstrated that vasoconstrictor agents increase intracellular Ca2+ and activate protein kinase C (PKC) to elevate vascular tone. The aim of the present study was to determine the importance of these signaling pathways for angiotensin II (ANG II) and thromboxane A2(TxA2) in regulating mesenteric blood flow (MBF) in vivo.
Gesehen am 08.12.2020